Mobilidade geográfica de trabalhadores qualificados: principais evidências para o Brasil e o Espírito Santo - Campos, João Paulo de Souza (2014)
The purpose of this dissertation, in general, was empirically estimate the probability of interstate migration of skilled workers to Brazil. We considered both variables concerning the individual as related to regional factors origin and destination of immigrants and the analyzes were made for the years 2001, 2006 and 2011. Probit and Logit Models were used to estimate the coefficient of the explanatory variables. The databases used were the PNAD and the main results show that the main pole of attraction of skilled workers is the state of São Paulo. In general the probability of migration of skilled workers is higher for male individuals, white and unmarried sex. Younger and higher income people are also more likely to be skilled immigrants.